Fizioterapevtska obravnava ahilove tendinopatije tekačev - Kopše, Eva Ivana (Delo in varnost, 2022)
Achilles tendinopathy is one of the most common overuse injuries in running, characterized by pain, reduced performance, and swelling in and around the tendon. Purpose: The purpose of this paper is to review the literature on the effectiveness of physical therapy exercises in the treatment of achilles tendinopathy in runners. Methods: A descriptive method based on a review of the scientific literature in the PubMed and PEDro databases is used. According to the PRISMA diagram, 10 scientific studies are included in the final analysis. The inclusion criteria used in the selection of articles were randomized control studies examining the effectiveness of physical therapy exercise in the treatment of Achilles tendinopathy in runners. Results: We found reliable scientific evidence on the effectiveness of physiotherapy exercise in the treatment of achilles tendinopathy in runners. Conclusion: The presentation of the effectiveness of physiotherapeutic exercises can contribute to the prevention and awareness of athletes and the further reduction of Achilles tendinopathy symptoms.
Keywords: achilles tendinopathy; ahilova tendinopatija; exercise; fizioterapija; physiotherapy; runners; tekači; vadba